2011
DOI: 10.1007/s00586-011-1880-9
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical motion in L5-S1 adult spondylolytic spondylolisthesis

Abstract: Introduction In patients with spondylolisthesis, it is assumed that flexion accentuates anterior displacement, whereas extension causes some reduction. Paradoxical movement-where flexion causes reduction of spondylolisthesis and extension increases the anterior translation, is rarely described. In this study, we investigate the prevalence of paradoxical motion in patients with L5-S1 spondylolytic spondylolisthesis and why this abnormal motion occurs. Materials and methods Flexion and extension radiographs of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…These findings reveal that patients in the DS group sustained more anterior instability. Indeed, we also found that some patients in the IS group (data not shown in the present study) had paradoxical motion, as Oh et al described[ 27 ]. In paradoxical movement, flexion reduces spondylolisthesis while extension increases anterior listhesis.…”
Section: Discussionsupporting
confidence: 88%
“…These findings reveal that patients in the DS group sustained more anterior instability. Indeed, we also found that some patients in the IS group (data not shown in the present study) had paradoxical motion, as Oh et al described[ 27 ]. In paradoxical movement, flexion reduces spondylolisthesis while extension increases anterior listhesis.…”
Section: Discussionsupporting
confidence: 88%
“…However, the inverse has also been reported as early as 1944 by Knuttson et al who found 4 cases of retrolisthesis of the superior vertebral body on forward bending at the L5/S1 segment[25]. This phenomenon has more recently been described in patients with spondylolytic spondylolisthesis[26]. One study showed that nearly half of patients analyzed with spondylolytic spondylolisthesis displayed this so-called “paradoxical motion” via measurement of instantaneous center of rotation, with displacements ranging from 0.5 to 4.5 mm[27].…”
Section: Discussionmentioning
confidence: 84%
“…Axial loading causes a reduction in the area and diameter of the dural sac at L3/L4 and L4/L5, and, to a lesser extent, at the level of the lumbar spine than L5/S1, which is probably due to paradoxical motion exerted at this level (17).…”
Section: Discussionmentioning
confidence: 98%